2022
DOI: 10.1186/s13047-021-00507-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical imaging for plantar heel pain: a systematic review and meta‐analysis

Abstract: Background Medical imaging can be used to assist with the diagnosis of plantar heel pain. The aim of this study was to synthesise medical imaging features associated with plantar heel pain. Methods This systematic review and meta-analysis conducted searches in MEDLINE, CINAHL, SPORTDiscus, Embase and the Cochrane Library from inception to 12th February 2021. Peer-reviewed articles of cross-sectional observational studies written in English that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 97 publications
(239 reference statements)
0
10
0
1
Order By: Relevance
“…However, only 2% of imaged heels (4 of 215 heels) in patients with atraumatic plantar heel pain have radiographic findings that affect initial treatments . A meta-analysis of 21 observational studies on medical imaging (1199 participants) demonstrated an association between ultrasonography-measured thickness of the plantar fascia in plantar fasciitis compared with controls (mean difference [MD], 2.00 mm [95% CI, 1.62-2.39]; P < .001) . MRI shows a T2-weighted hyperintensity in the origin of the plantar fascia at the calcaneal tuberosity as well as thickening of the plantar fascia, but should only be used when the clinical diagnosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 2% of imaged heels (4 of 215 heels) in patients with atraumatic plantar heel pain have radiographic findings that affect initial treatments . A meta-analysis of 21 observational studies on medical imaging (1199 participants) demonstrated an association between ultrasonography-measured thickness of the plantar fascia in plantar fasciitis compared with controls (mean difference [MD], 2.00 mm [95% CI, 1.62-2.39]; P < .001) . MRI shows a T2-weighted hyperintensity in the origin of the plantar fascia at the calcaneal tuberosity as well as thickening of the plantar fascia, but should only be used when the clinical diagnosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the supination resistance in PF was not significantly different from the healthy counterparts. Plantar fasciopathy is characterised by microtears in a thickened plantar fascia [48], but unlike PTTD and CAI, PF does not usually lead to ligamentous or muscles injuries [48,49]. It appears that one important factor that could influence supination resistance is foot and ankle mobility/ rigidity and that the specific structures affected in PF do not have a direct impact on supination resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 31 The diagnosis of plantar fasciitis was based on tenderness at the medial insertion of the plantar fascia to the calcaneus and the thickness of >4.0 mm on magnetic resonance imaging (MRI). 10 , 17 After failing to respond to >6 months of conservative treatment, the patients with plantar fasciitis underwent endoscopic CSR with or without PFR. Patients with a calcaneal spur ≥2 mm underwent endoscopic CSR alone, and those with a calcaneal spur <2 mm underwent endoscopic PFR combined with CSR.…”
Section: Methodsmentioning
confidence: 99%